"Cleaning Out the Closet:" Communicated Narrative Sense-Making of Bereavement. Issue 4 (2nd October 2021) - Barney, Kendyl A.; Yoshimura, Christina G.
ABSTRACT: Communicated Narrative Sense-Making Theory was applied to 14 semi-structured interviews to explore stories of sorting through a deceased family member's belongings/changing the home after death ("cleaning out the closet"). Family stories about "cleaning out the closet" yielded retrospective storytelling content themes regarding why changes were made/not made, how family members communicated when deciding to make any changes, and what changed or didn't change as a result of "cleaning out the closet." These results advance the claim that "cleaning out the closet" functions as a unique site where the instrumental task meets narrative communication openings for families, and that this task offers key opportunities for sense-making, socialization, and well-being during the turbulent period of bereavement.